A chemical strengthening method for flexible glass and chemically strengthened flexible glass

By adopting the exchange technology of chemically strengthening pure sodium molten salt in flexible glass, the problem of flexible glass strengthening with low Na ion content and high Li ion content is solved, and the glass strength and appearance quality are improved, the product yield rate is improved and the production cost is reduced.

CN119306405BActive Publication Date: 2025-04-15CAIHONG GRP SHAOYANG SPECIAL GLASS CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411879787.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-04-15
Estimated Expiration
2044-12-19

AI Technical Summary

Technical Problem

The prior art is difficult to effectively strengthen flexible glass with low Na ion content and high Li ion content in the glass material, resulting in high internal tension stress, self-detonation and failure to meet the appearance quality.

Method used

Chemically strengthened pure sodium molten salt is used to chemically strengthen the flexible glass. By exchanging the pretreatment and preheated flexible glass with the chemically strengthened pure sodium molten salt, the Na ion concentration inside the glass is improved, thereby improving the strength and appearance quality of the glass.

Benefits of technology

Effectively improve the strength and appearance quality of flexible glass, improve product yield, reduce production costs, and show excellent performance in bending strength, pen impact, flatness and static bending times.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119306405B_ABST
    Figure CN119306405B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of glass technology, and specifically to a method for chemically strengthening flexible glass and chemically strengthened flexible glass. The method for chemically strengthening flexible glass comprises the following steps: pre-treating the flexible glass to obtain pre-treated flexible glass; preheating the pre-treated flexible glass to obtain pre-heated flexible glass; placing the pre-heated flexible glass in a chemically strengthened pure sodium molten salt for chemical strengthening treatment and then cooling to obtain chemically strengthened flexible glass; the pre-treatment comprises: ultrasonically treating the flexible glass in a sodium hydroxide alkaline solution with a concentration of 4-12 mol / L; in the flexible glass raw material, in terms of molar percentage, Na2O 0-3%, Li2O 8-10%. The present application can effectively improve the strength of the flexible glass, which is beneficial to overcome the damage to the glass surface caused by stress concentration; the chemically strengthened flexible glass exhibits excellent performance in bending strength, pen impact, and 300,000 static bending.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of glass preparation, and in particular to a chemical strengthening method for flexible glass and chemically strengthened flexible glass. Background Art

[0002] As an important raw material for flexible screens, flexible glass has the advantages of being ultra-thin, bendable, resilient, flexible, wear-resistant, and strong, and is gradually being used in products such as solar cells, display substrates, and folding screen covers. Flexible glass products with a thickness of 100μm or less can achieve foldable performance, but the smaller the thickness, the more difficult it is to produce the glass and the lower the yield rate.

[0003] At present, the purpose of chemical strengthening of conventional glass is mainly to improve the impact resistance, surface hardness, and drop resistance of glass. However, the chemical strengthening of flexible glass pays more attention to the appearance quality and bending ability of glass while ensuring strength. The existing strengthening process of flexible glass is to use pure potassium salt to chemically strengthen the flexible glass, thereby obtaining a higher surface compressive stress (CS), resulting in a higher internal tensile stress (CT), and prone to self-explosion and rupture, and appearance quality that does not meet the standards, resulting in a final yield rate of less than 60%, greatly increasing production costs and affecting the widespread application of flexible glass with a thickness of less than or equal to 100μm. At the same time, the strengthening process of pure potassium salt is not suitable for glass with a low Na ion content and a high Li ion content in the material, mainly because the difference in ion radius is too large, and Na ions and Li ions are more difficult to exchange ions. Summary of the invention

[0004] The object of the present invention is to provide a method for chemically strengthening flexible glass, which is used to solve the problem in the prior art that ion exchange is difficult to perform when the Na ion content in the glass material is low and the Li ion content is high.

[0005] The present invention also provides a chemically strengthened flexible glass to solve the problem in the prior art that ion exchange is difficult to perform when the Na ion content in the glass material is low and the Li ion content is high.

[0006] In order to solve the above problems, the present invention proposes a chemical strengthening method for flexible glass, and the technical solution adopted is:

[0007] A method for chemically strengthening flexible glass comprises the following steps: firstly pre-treating the flexible glass to obtain pre-treated flexible glass; then preheating the pre-treated flexible glass to obtain pre-heated flexible glass; finally placing the pre-heated flexible glass in a chemically strengthened pure sodium molten salt for chemical strengthening treatment and then cooling to obtain the chemically strengthened flexible glass;

[0008] The pretreatment comprises: subjecting the flexible glass to ultrasonic treatment in a sodium hydroxide alkaline solution with a concentration of 4 to 12 mol / L;

[0009] In terms of molar percentage, the raw materials of the flexible glass include: Na 2 O. Li 2 O、SiO 2 、Al 2 O 3 , B 2 O 3 , K 2 O, MgO, CaO, SrO, BaO, P 2 O 5 、ZrO 2 、TiO 2 ,La 2 O 3 and Y 2 O 3 , where Na 2 O 0%~3%, Li 2 O 8%~10%, SiO 2 62%,Al 2 O 3 23%, and other raw materials 2% to 7%.

[0010] The beneficial effects of the present invention are as follows: the present invention is directed to flexible glass with extremely low Na ion content or no Na ion, by adopting chemically strengthened pure sodium molten salt, during the process of chemically strengthening the flexible glass, the Li ion content in the flexible glass is relatively high, and for flexible glass with extremely low Na ion content or no Na ion, the Na ion content in the chemically strengthened pure sodium molten salt is relatively high, according to the Gibbs free energy theory and the concentration difference theory, the high concentration of ions will spontaneously migrate to the low concentration direction, and the Na ions and Li ions are fully exchanged, thereby increasing the internal Na ion concentration of the product, and then achieving the purpose of chemical strengthening, and obtaining chemically strengthened flexible glass. The chemical strengthening method of the flexible glass of the present invention can effectively improve the strength of the flexible glass, thereby facilitating overcoming the destructive effect of stress concentration on the glass surface; the flexible glass after chemical strengthening shows excellent performance in bending strength, pen impact, flatness, 300,000 static bending, etc., and can improve the appearance quality of the flexible glass, improve the overall yield rate of the product, and reduce production costs. Among them, using alkaline solution to ultrasonically clean flexible glass can effectively remove surface dirt, improve the surface wettability of the glass, and effectively enhance the ion exchange capacity during the chemical strengthening process.

[0011] In order to obtain chemically strengthened pure sodium molten salt, preferably, the method for preparing the chemically strengthened pure sodium molten salt comprises the following steps: heating pure sodium salt to a temperature for chemical strengthening treatment to obtain the chemically strengthened pure sodium molten salt.

[0012] In order to obtain chemically strengthened pure sodium molten salt at low cost and conveniently, preferably, the pure sodium salt is pure sodium nitrate.

[0013] In order to fully exchange Na ions and Li ions, increase the stress depth of the flexible glass and reduce surface deformation, preferably, the temperature of the chemical strengthening treatment is 350-500° C. and the time is 30-480 min.

[0014] In order to shorten the temperature difference between the flexible glass and the chemically strengthened pure sodium molten salt during chemical strengthening, reduce the tensile stress caused by the temperature difference, and further avoid the generation of defects and deformation caused by tensile stress, preferably, the preheating temperature is 350-450°C and the time is 30-90 minutes. The setting of the preheating temperature combines the energy consumption factor and the final yield to ensure that it meets expectations while reducing costs.

[0015] In order to use an alkaline solution to fully ultrasonically clean the flexible glass, preferably, the temperature of the ultrasonic treatment is 30-60° C., and the frequency of the ultrasonic treatment is 40-120 KHZ.

[0016] In order to lower the temperature of the chemically strengthened flexible glass and reduce the defects of the chemically strengthened flexible glass, preferably, the cooling includes cooling and natural cooling, the cooling rate is 2 ~ 5 ° C / min, the cooling is cooled to a temperature of 100 ~ 105 ° C; then naturally cooled to the temperature of ambient temperature.

[0017] The present invention also proposes a chemically strengthened flexible glass, the technical solution adopted is:

[0018] A chemically strengthened flexible glass is obtained by subjecting the flexible glass to chemical strengthening treatment according to the above-mentioned chemical strengthening method for flexible glass.

[0019] The beneficial effects of the present invention are as follows: the chemically strengthened flexible glass prepared by the chemical strengthening method of the present invention exhibits excellent performance in terms of bending strength, pen impact, flatness, 300,000 static bending times, etc., and can improve the appearance quality of the flexible glass, improve the overall product yield, and reduce production costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 It is a schematic flow chart of the chemical strengthening method of flexible glass in the present invention. DETAILED DESCRIPTION

[0021] In the prior art, it is difficult to perform ion exchange when the Na ion content in the glass material is low and the Li ion content is high. The present invention provides a method for chemically strengthening flexible glass, comprising the following steps: first pre-treating the flexible glass to obtain pre-treated flexible glass; then pre-heating the pre-treated flexible glass to obtain pre-heated flexible glass; finally placing the pre-heated flexible glass in a chemically strengthened pure sodium molten salt for chemical strengthening treatment and then cooling to obtain a chemically strengthened flexible glass;

[0022] The pretreatment comprises: subjecting the flexible glass to ultrasonic treatment in a sodium hydroxide alkaline solution with a concentration of 4 to 12 mol / L;

[0023] In terms of molar percentage, the raw materials of the flexible glass include: Na 2 O. Li 2 O、SiO 2 、Al 2 O 3 , B 2 O 3 , K 2 O, MgO, CaO, SrO, BaO, P 2 O 5 、ZrO 2 、TiO 2 ,La 2 O 3 and Y 2 O 3 , where Na 2 O 0%~3%, Li 2 O 8%~10%, SiO 2 62%,Al 2 O 3 23%, and other raw materials 2% to 7%.

[0024] The technical concept of the present invention is: for flexible glass with extremely low Na ion content or no Na ion, the preheated flexible glass shortens the temperature difference between the flexible glass and the chemically strengthened pure sodium molten salt during chemical strengthening; by using chemically strengthened pure sodium molten salt, during the chemical strengthening process of the flexible glass, the Li ion content in the flexible glass is relatively high, and for flexible glass with extremely low Na ion content or no Na ion, the Na ion content in the chemically strengthened pure sodium molten salt is relatively high. According to the Gibbs free energy theory and the concentration difference theory, high-concentration ions will spontaneously migrate to the low-concentration direction, and Na ions and Li ions are fully exchanged, thereby increasing the internal Na ion concentration of the product, and achieving the purpose of chemical strengthening, and obtaining chemically strengthened flexible glass. The flexible glass prepared by the chemical strengthening method of the present invention shows excellent performance in bending strength, pen impact, flatness, 300,000 static bending, etc., and can improve the appearance quality of the flexible glass, improve the overall yield of the product, and reduce production costs. The chemically strengthened flexible glass prepared by the present application has good flexible properties such as bending and folding, and is suitable for making flexible screens and related equipment.

[0025] Specifically, Figure 1 As shown, the chemical strengthening method of flexible glass comprises the following steps:

[0026] First, the flexible glass is pretreated, that is, the flexible glass is ultrasonically treated in a sodium hydroxide alkaline solution with a concentration of 4 to 12 mol / L, wherein the ultrasonic treatment temperature is 30 to 60°C, the ultrasonic treatment frequency is 40 to 120 KHZ, and the ultrasonic treatment time is 3 minutes;

[0027] Secondly, the pretreated flexible glass is placed in a preheating furnace for preheating, that is, the ultrasonically treated flexible glass is placed in a preheating furnace for preheating, wherein the preheating temperature is 350-450°C and the time is 30-120 minutes;

[0028] Next, 100% pure sodium nitrate salt is added into the tempering furnace and heated to a temperature for chemical strengthening treatment to obtain chemically strengthened pure sodium molten salt, wherein the temperature for chemical strengthening treatment is 350-500°C;

[0029] Then, the preheated flexible glass is placed in a chemically strengthened pure sodium molten salt for chemical strengthening treatment, and the temperature is kept for a certain period of time so that the Na ions in the molten salt are fully exchanged with the Li ions inside the flexible glass to obtain the chemically strengthened flexible glass; wherein the temperature of the chemical strengthening treatment is 350-500°C and the time is 30-480min;

[0030] Finally, the chemically strengthened flexible glass is cooled to 100-105°C at a cooling rate of 2-5°C / min, and then naturally cooled to ambient temperature to complete chemical strengthening and obtain the target glass, i.e., chemically strengthened flexible glass.

[0031] The chemically strengthened flexible glass prepared by the chemical strengthening method of flexible glass provided by the present invention is mainly used for flexible glass products, such as flexible screens and the like.

[0032] The implementation process of the present invention is described in detail below in conjunction with specific embodiments. However, it will be appreciated by those skilled in the art that the following embodiments are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. It should also be noted that, for ease of description, only the parts related to the invention are shown in the embodiments.

[0033] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present application will be described in detail with reference to the embodiments below.

[0034] It should be noted that the endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed in this article.

[0035] In the following examples and comparative examples, the thickness of the flexible glass is 30 μm, and the raw materials used are all common commercial products that can be directly purchased or can be prepared according to conventional techniques in the art.

[0036] 1. Embodiment of the method for chemically strengthening flexible glass of the present invention

[0037] Example 1

[0038] The chemical strengthening method of flexible glass provided in this embodiment includes the following steps:

[0039] First, the flexible glass was subjected to ultrasonic treatment in a sodium hydroxide alkaline solution with a concentration of 4 mol / L, wherein the ultrasonic treatment temperature was 30° C., the ultrasonic treatment frequency was 40 KHZ, and the ultrasonic treatment time was 3 min;

[0040] Secondly, the ultrasonically treated flexible glass was placed in a preheating furnace for preheating, wherein the preheating temperature was 350°C and the preheating time was 30 minutes;

[0041] Next, 100% pure sodium nitrate salt is added into the tempering furnace and the temperature is raised to the temperature of chemical strengthening treatment to obtain chemically strengthened pure sodium molten salt, wherein the temperature of chemical strengthening treatment is 350°C;

[0042] Then, the preheated flexible glass is placed in a chemically strengthened pure sodium molten salt for chemical strengthening treatment, so that the Na + Li inside the flexible glass + The flexible glass is fully exchanged to obtain a chemically strengthened flexible glass; wherein the chemical strengthening treatment is performed at a temperature of 350°C and a time of 480 minutes;

[0043] Finally, the chemically strengthened flexible glass was cooled to 100°C at a cooling rate of 2°C / min, and then naturally cooled to ambient temperature to obtain the chemically strengthened flexible glass.

[0044] In this embodiment, the raw materials of the flexible glass include, in mole percentage: Na 2 O. Li 2 O、SiO 2 、Al 2 O 3 , B 2 O 3 , K 2 O, MgO, CaO, SrO, BaO, P 2 O 5 、ZrO 2 、TiO 2 ,La 2 O 3 and Y 2 O 3 , where Na 2 O 0%,Li 2 O 10%, SiO 2 62%,Al 2 O 3 23% and other raw materials 5%.

[0045] Example 2

[0046] The chemical strengthening method of flexible glass provided in this embodiment includes the following steps:

[0047] First, the flexible glass was subjected to ultrasonic treatment in a sodium hydroxide alkaline solution with a concentration of 6 mol / L, wherein the ultrasonic treatment temperature was 40° C., the ultrasonic treatment frequency was 50 KHZ, and the ultrasonic treatment time was 3 min;

[0048] Secondly, the flexible glass after ultrasonic treatment is placed in a preheating furnace for preheating, wherein the preheating temperature is 400°C and the preheating time is 90 minutes;

[0049] Next, 100% pure sodium nitrate salt is added into the tempering furnace and heated to a temperature for chemical strengthening treatment to obtain chemically strengthened pure sodium molten salt, wherein the temperature for chemical strengthening treatment is 400°C;

[0050] Then, the preheated flexible glass is placed in a chemically strengthened pure sodium molten salt for chemical strengthening treatment, so that the Na + Li inside the flexible glass + The flexible glass is fully exchanged to obtain a chemically strengthened flexible glass; wherein the chemical strengthening treatment is performed at a temperature of 450°C and a time of 180 minutes;

[0051] Finally, the chemically strengthened flexible glass was cooled to 100°C at a cooling rate of 5°C / min, and then naturally cooled to ambient temperature to obtain the chemically strengthened flexible glass.

[0052] In this embodiment, the raw materials of the flexible glass include, in mole percentage: Na 2 O. Li 2 O、SiO 2 、Al 2 O 3 , B 2 O 3 , K 2 O, MgO, CaO, SrO, BaO, P 2 O 5 、ZrO 2 、TiO 2 ,La 2 O 3 and Y 2 O 3 , where Na 2 O 0.5%, Li 2 O 9%, SiO 2 62%,Al 2 O 3 23% and other raw materials 5.5%.

[0053] Example 3

[0054] The chemical strengthening method of flexible glass provided in this embodiment includes the following steps:

[0055] First, the flexible glass was subjected to ultrasonic treatment in a sodium hydroxide alkaline solution with a concentration of 6 mol / L, wherein the ultrasonic treatment temperature was 40° C., the ultrasonic treatment frequency was 50 KHZ, and the ultrasonic treatment time was 3 min;

[0056] Secondly, the ultrasonically treated flexible glass is placed in a preheating furnace for preheating, wherein the preheating temperature is 450°C and the preheating time is 90 minutes;

[0057] Next, 100% pure sodium nitrate salt is added into the tempering furnace and heated to a temperature for chemical strengthening treatment to obtain chemically strengthened pure sodium molten salt, wherein the temperature for chemical strengthening treatment is 400°C;

[0058] Then, the preheated flexible glass is placed in a chemically strengthened pure sodium molten salt for chemical strengthening treatment, so that the Na + Li inside the flexible glass + The flexible glass is fully exchanged to obtain a chemically strengthened flexible glass; wherein the chemical strengthening treatment is performed at a temperature of 450°C and a time of 300 minutes;

[0059] Finally, the chemically strengthened flexible glass was cooled to 100°C at a cooling rate of 5°C / min, and then naturally cooled to ambient temperature to obtain the chemically strengthened flexible glass.

[0060] In this embodiment, the raw materials of the flexible glass include, in mole percentage: Na 2 O. Li 2 O、SiO 2 、Al 2 O 3 , B 2 O 3 , K 2 O, MgO, CaO, SrO, BaO, P 2 O 5 、ZrO 2 、TiO 2 ,La 2 O 3 and Y 2 O 3 , where Na 2 O 1%, Li 2 O 8%, SiO 2 62%,Al 2 O 3 23% and other raw materials 6%.

[0061] Example 4

[0062] The chemical strengthening method of flexible glass provided in this embodiment includes the following steps:

[0063] First, the flexible glass was subjected to ultrasonic treatment in an 8 mol / L sodium hydroxide alkaline solution, wherein the ultrasonic treatment temperature was 40° C., the ultrasonic treatment frequency was 50 KHZ, and the ultrasonic treatment time was 3 min;

[0064] Secondly, the flexible glass after ultrasonic treatment is placed in a preheating furnace for preheating, wherein the preheating temperature is 400°C and the preheating time is 90 minutes;

[0065] Next, 100% pure sodium nitrate salt is added into the tempering furnace and the temperature is raised to the temperature of chemical strengthening treatment to obtain chemically strengthened pure sodium molten salt, wherein the temperature of chemical strengthening treatment is 450°C;

[0066] Then, the preheated flexible glass is placed in a chemically strengthened pure sodium molten salt for chemical strengthening treatment, so that the Na + Li inside the flexible glass + The flexible glass is fully exchanged to obtain a chemically strengthened flexible glass; wherein the chemical strengthening treatment is performed at a temperature of 500°C and a time of 120 minutes;

[0067] Finally, the chemically strengthened flexible glass was cooled to 100°C at a cooling rate of 5°C / min, and then naturally cooled to ambient temperature to obtain the chemically strengthened flexible glass.

[0068] In this embodiment, the raw materials of the flexible glass include, in mole percentage: Na 2 O. Li 2 O、SiO 2 、Al 2 O 3 , B 2 O 3 , K 2 O, MgO, CaO, SrO, BaO, P 2 O 5 、ZrO 2 、TiO 2 ,La 2 O 3 and Y 2 O 3 , where Na 2 O 1%, Li 2 O 8%, SiO 2 62%,Al 2 O 3 23% and other raw materials 6%.

[0069] Example 5

[0070] The chemical strengthening method of flexible glass provided in this embodiment includes the following steps:

[0071] First, the flexible glass was subjected to ultrasonic treatment in an 8 mol / L sodium hydroxide alkaline solution, wherein the ultrasonic treatment temperature was 40° C., the ultrasonic treatment frequency was 50 KHZ, and the ultrasonic treatment time was 3 min;

[0072] Secondly, the flexible glass after ultrasonic treatment is placed in a preheating furnace for preheating, wherein the preheating temperature is 400°C and the preheating time is 90 minutes;

[0073] Next, 100% pure sodium nitrate salt is added into the tempering furnace and the temperature is raised to the temperature of chemical strengthening treatment to obtain chemically strengthened pure sodium molten salt, wherein the temperature of chemical strengthening treatment is 450°C;

[0074] Then, the preheated flexible glass is placed in a chemically strengthened pure sodium molten salt for chemical strengthening treatment, so that the Na + Li inside the flexible glass + The flexible glass is fully exchanged to obtain a chemically strengthened flexible glass; wherein the chemical strengthening treatment temperature is 500°C and the time is 180 minutes;

[0075] Finally, the chemically strengthened flexible glass was cooled to 100°C at a cooling rate of 5°C / min, and then naturally cooled to ambient temperature to obtain the chemically strengthened flexible glass.

[0076] In this embodiment, the raw materials of the flexible glass include, in mole percentage: Na 2 O. Li 2 O、SiO 2 、Al 2 O 3 , B 2 O 3 , K 2 O, MgO, CaO, SrO, BaO, P 2 O 5 、ZrO 2 、TiO 2 ,La 2 O 3 and Y 2 O 3 , where Na 2 O 1%, Li 2 O 8%, SiO 2 62%,Al 2 O 3 23% and other raw materials 6%.

[0077] Example 6

[0078] The chemical strengthening method of flexible glass provided in this embodiment includes the following steps:

[0079] First, the flexible glass was subjected to ultrasonic treatment in a sodium hydroxide alkaline solution with a concentration of 10 mol / L, wherein the ultrasonic treatment temperature was 40° C., the ultrasonic treatment frequency was 50 KHZ, and the ultrasonic treatment time was 3 min;

[0080] Secondly, the flexible glass after ultrasonic treatment is placed in a preheating furnace for preheating, wherein the preheating temperature is 400°C and the preheating time is 90 minutes;

[0081] Next, 100% pure sodium nitrate salt is added into the tempering furnace and heated to a temperature for chemical strengthening treatment to obtain chemically strengthened pure sodium molten salt, wherein the temperature for chemical strengthening treatment is 400°C;

[0082] Then, the preheated flexible glass is placed in a chemically strengthened pure sodium molten salt for chemical strengthening treatment, so that the Na + Li inside the flexible glass + The flexible glass is fully exchanged to obtain a chemically strengthened flexible glass; wherein the chemical strengthening treatment temperature is 500°C and the time is 240 minutes;

[0083] Finally, the chemically strengthened flexible glass was cooled to 100°C at a cooling rate of 5°C / min, and then naturally cooled to ambient temperature to obtain the chemically strengthened flexible glass.

[0084] In this embodiment, the raw materials of the flexible glass include, in mole percentage: Na 2 O. Li 2 O、SiO 2 、Al 2 O 3 , B 2 O 3 , K 2 O, MgO, CaO, SrO, BaO, P 2 O 5 、ZrO 2 、TiO 2 ,La 2 O 3 and Y 2 O 3 , where Na 2 O 1%, Li 2 O 8%, SiO 2 62%,Al 2 O 3 23% and other raw materials 6%.

[0085] Example 7

[0086] The chemical strengthening method of flexible glass provided in this embodiment includes the following steps:

[0087] First, the flexible glass was subjected to ultrasonic treatment in a sodium hydroxide alkaline solution with a concentration of 10 mol / L, wherein the ultrasonic treatment temperature was 60° C., the ultrasonic treatment frequency was 50 KHZ, and the ultrasonic treatment time was 3 min;

[0088] Secondly, the flexible glass after ultrasonic treatment is placed in a preheating furnace for preheating, wherein the preheating temperature is 400°C and the preheating time is 90 minutes;

[0089] Next, 100% pure sodium nitrate salt is added into the tempering furnace and heated to a temperature for chemical strengthening treatment to obtain chemically strengthened pure sodium molten salt, wherein the temperature for chemical strengthening treatment is 400°C;

[0090] Then, the preheated flexible glass is placed in a chemically strengthened pure sodium molten salt for chemical strengthening treatment, so that the Na + Li inside the flexible glass + The flexible glass is fully exchanged to obtain a chemically strengthened flexible glass; wherein the chemical strengthening treatment temperature is 500°C and the time is 300 minutes;

[0091] Finally, the chemically strengthened flexible glass was cooled to 100°C at a cooling rate of 5°C / min, and then naturally cooled to ambient temperature to obtain the chemically strengthened flexible glass.

[0092] In this embodiment, the raw materials of the flexible glass include, in mole percentage: Na 2 O. Li 2 O、SiO 2 、Al 2 O 3 , B 2 O 3 , K 2 O, MgO, CaO, SrO, BaO, P 2 O 5 、ZrO 2 、TiO 2 ,La 2 O 3 and Y 2 O 3 , where Na 2 O 1%, Li 2 O 8%, SiO 2 62%,Al 2 O 3 23% and other raw materials 6%.

[0093] Example 8

[0094] The chemical strengthening method of flexible glass provided in this embodiment includes the following steps:

[0095] First, the flexible glass was subjected to ultrasonic treatment in a sodium hydroxide alkaline solution with a concentration of 12 mol / L, wherein the ultrasonic treatment temperature was 40° C., the ultrasonic treatment frequency was 120 KHZ, and the ultrasonic treatment time was 3 min;

[0096] Secondly, the flexible glass after ultrasonic treatment is placed in a preheating furnace for preheating, wherein the preheating temperature is 400°C and the preheating time is 90 minutes;

[0097] Next, 100% pure sodium nitrate salt is added into the tempering furnace and the temperature is raised to the temperature of chemical strengthening treatment to obtain chemically strengthened pure sodium molten salt, wherein the temperature of chemical strengthening treatment is 450°C;

[0098] Then, the preheated flexible glass is placed in a chemically strengthened pure sodium molten salt for chemical strengthening treatment, so that the Na + Li inside the flexible glass + The flexible glass is fully exchanged to obtain a chemically strengthened flexible glass; wherein the chemical strengthening treatment is performed at a temperature of 500°C and for 30 minutes;

[0099] Finally, the chemically strengthened flexible glass was cooled to 100°C at a cooling rate of 5°C / min, and then naturally cooled to ambient temperature to obtain the chemically strengthened flexible glass.

[0100] In this embodiment, the raw materials of the flexible glass include, in mole percentage: Na 2 O. Li 2 O、SiO 2 、Al 2 O 3 , B 2 O 3 , K 2 O, MgO, CaO, SrO, BaO, P 2 O 5 、ZrO 2 、TiO 2 ,La 2 O 3 and Y 2 O 3 , where Na 2 O 3%, Li 2 O 8%, SiO 2 62%,Al 2 O 3 23% and other raw materials 4%.

[0101] 2. Comparison

[0102] Comparative Example 1

[0103] The chemical strengthening method of flexible glass provided in this comparative example is different from that in Example 1 in that 100% pure potassium nitrate is used to prepare the molten salt.

[0104] Comparative Example 2

[0105] The chemical strengthening method of flexible glass provided in this comparative example is different from that in Example 2 in that 100% pure potassium nitrate is used to prepare the molten salt.

[0106] Comparative Example 3

[0107] The chemical strengthening method of flexible glass provided in this comparative example is different from that in Example 3 in that 100% pure potassium nitrate is used to prepare the molten salt.

[0108] Comparative Example 4

[0109] The chemical strengthening method of flexible glass provided in this comparative example is different from that of Example 4 in that 100% pure potassium nitrate is used to prepare the molten salt.

[0110] Comparative Example 5

[0111] The chemical strengthening method of flexible glass provided in this comparative example is different from that in Example 5 in that 100% pure potassium nitrate is used to prepare the molten salt.

[0112] Comparative Example 6

[0113] The chemical strengthening method of flexible glass provided in this comparative example is different from that of Example 6 in that 100% pure potassium nitrate is used to prepare the molten salt.

[0114] Comparative Example 7

[0115] The chemical strengthening method of flexible glass provided in this comparative example is different from that in Example 7 in that 100% pure potassium nitrate is used to prepare the molten salt.

[0116] Comparative Example 8

[0117] The chemical strengthening method of flexible glass provided in this comparative example is different from that of Example 8 in that 100% pure potassium nitrate is used to prepare the molten salt.

[0118] Comparative Example 9

[0119] The chemical strengthening method of the flexible glass provided in this comparative example is different from that in Example 1 in that the raw materials of the flexible glass contain Na 2 The mole percentage of O is 4%.

[0120] Comparative Example 10

[0121] The chemical strengthening method of the flexible glass provided in this comparative example is different from that in Example 1 in that the raw materials of the flexible glass contain Na 2 The mole percentage of O is 5%.

[0122] 3. Experimental Examples

[0123] Experimental Example 1

[0124] The Na of the flexible glass in the above Examples 1-8 and Comparative Examples 1-10 before and after chemical strengthening 2 O content and Li 2 O content detection. Specifically, the detection method is: electron probe scanning. The detection results are shown in Table 1 and Table 2:

[0125] Table 1 Na of the flexible glass in Examples 1-8 before and after chemical strengthening 2 O content and Li 2 O content

[0126]

[0127] Table 2 Na before and after chemical strengthening of the flexible glass in Examples 1-10 2 O content and Li 2 O content

[0128]

[0129] It can be seen from Table 1 that the Na of the flexible glass in Examples 1-8 of the present application before and after chemical strengthening 2 As the O content increases, Li 2 The decrease in O content indicates that in the chemical strengthening method of the flexible glass, the Na ions in the chemically strengthened pure sodium molten salt and the Li ions in the flexible glass raw material are fully exchanged, thereby increasing the Na ion concentration inside the flexible glass and reducing the Li ion concentration inside the flexible glass. 2 O content remains unchanged, Na 2 The O content remains basically unchanged, indicating that the Na ions and Li ions are not exchanged in the chemical strengthening method of the flexible glass.

[0130] Experimental Example 2

[0131] The chemically strengthened flexible glasses obtained in the above Examples 1-8 and Comparative Examples 1-10 were subjected to physical and chemical property tests.

[0132] Specifically, the appearance defect detection of chemically strengthened flexible glass: use a polarizing microscope, Aihua MOTICBA310-MET-S, to observe the product under the polarizing microscope. If the defect radius of the chemically strengthened flexible glass is >0.5mm, the product is considered to have a concave-convex defect.

[0133] Bending strength test: Shangzhun universal material testing machine RS-N8000, during the bending strength test, a special fixture is used to clamp the chemically strengthened flexible glass, and the instrument steps forward from top to bottom until the product is crushed, and the bending radius of the product when the product is crushed is recorded. It is a destructive test, and the judgment standard is: when the bending radius is less than 1mm, the product is not broken, then the product is considered qualified (OK), otherwise the product is considered unqualified (NG).

[0134] Pen drop impact test: Shangzhun SA-8220V fully automatic pen drop impact tester, pen drop weight 8.6g, M&G 0.7mm pen core, hollow fixture, test starting from 3cm, raising 1cm each time and repeating the test until it breaks, to get the final pen drop impact height.

[0135] Surface hardness test: pencil hardness test.

[0136] Flatness test: CAV instrument, tests the height values ​​of multiple product points for calculation.

[0137] Static bending test: Fix the two ends of the long side of the product on the bending fatigue tester, set the reciprocating frequency of the tester to 30 times / min, and after the product reaches the bending radius, move the plate back to the starting position, complete one bending fatigue test, and then cycle the sample back and forth. The judgment standard is: if the static bending times are greater than 300,000 times and the product does not break, the product is considered qualified (OK), otherwise the product is considered unqualified (NG).

[0138] The specific test results are shown in Table 3 and Table 4:

[0139] Table 3 Performance test results of the chemically strengthened flexible glass prepared in Examples 1-8

[0140]

[0141] Table 4 Performance test results of chemically strengthened flexible glass prepared in Comparative Examples 1-10

[0142]

[0143] It can be seen from Table 3 that the appearance yield of the chemically strengthened flexible glass obtained by the chemical strengthening method of flexible glass in Examples 1-8 of the present application reaches more than 83%, and can reach up to 96%; in the bending strength test, the bending radius of the product is less than 1 mm, and the lowest can be 0.793 mm, and the product is qualified (OK); the height of the pen impact is above 40 cm, and the highest can reach 50 cm; the flatness is within 5μm; the surface hardness is above 5.0H, and the highest can reach 5.5H; the chemically strengthened flexible glass prepared in the examples of the present application remains unbroken when the number of static bending times is greater than 300,000 times, and the chemically strengthened flexible glass product is qualified (OK).

[0144] However, it can be seen from Table 4 that the appearance yield of the chemically strengthened flexible glass obtained by the chemical strengthening method of the flexible glass in Comparative Examples 1-10 is up to 39%; in the bending strength test, the bending radius of the product is greater than 1mm, and the product is unqualified (NG); the height of the pen impact is below 32cm, and the lowest is 10cm; the flatness is above 5μm; the surface hardness is below 4.5H; the chemically strengthened flexible glass prepared in the comparative example of the present application is broken when the number of static bending times is greater than 300,000 times, and the chemically strengthened flexible glass product is unqualified (NG). Therefore, the chemically strengthened flexible glass prepared in the comparative example has many appearance defects and low yield, and cannot meet production needs.

[0145] This shows that the chemically strengthened flexible glass prepared by the chemical strengthening method of flexible glass provided in the present application shows excellent performance in terms of appearance yield, bending strength, pen impact, flatness, 300,000 static bending times, etc., and can effectively improve the strength of the flexible glass, thereby helping to overcome the destructive effect of stress concentration on the glass surface. The strengthened flexible glass has good flexible properties such as bending or folding, and is suitable for making flexible screens and related equipment.

[0146] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for chemically strengthening flexible glass, characterized in that: The method comprises the following steps: firstly pre-treating the flexible glass to obtain pre-treated flexible glass; then pre-heating the pre-treated flexible glass to obtain pre-heated flexible glass; Finally, the preheated flexible glass is placed in a chemically strengthened pure sodium molten salt for chemical strengthening treatment and then cooled to obtain the chemically strengthened flexible glass; The pretreatment comprises: subjecting the flexible glass to ultrasonic treatment in a sodium hydroxide alkaline solution with a concentration of 4 to 12 mol / L; In terms of mole percentage, the raw materials of the flexible glass include: Na2O, Li2O, SiO2, Al2O3, B2O3, K2O, MgO, CaO, SrO, BaO, P2O5, ZrO2, TiO2, La2O3 and Y2O3, wherein Na2O accounts for 0% to 3%, Li2O accounts for 8% to 10%, SiO2 accounts for 62%, Al2O3 accounts for 23%, and the remaining raw materials account for 2% to 7%; The pure sodium salt is pure sodium nitrate; The temperature of the chemical strengthening treatment is 350-500°C.

2. The method for chemically strengthening flexible glass according to claim 1, characterized in that: The preparation method of the chemically strengthened pure sodium molten salt comprises the following steps: heating the pure sodium salt to a temperature for chemical strengthening treatment to obtain the chemically strengthened pure sodium molten salt.

3. The method for chemically strengthening flexible glass according to claim 2, characterized in that: The time of the chemical strengthening treatment is 30 to 480 minutes.

4. The method for chemically strengthening flexible glass according to claim 1, characterized in that: The preheating temperature is 350-450° C. and the preheating time is 30-90 minutes.

5. The method for chemically strengthening flexible glass according to claim 1, characterized in that: The temperature of the ultrasonic treatment is 30-60° C., and the frequency of the ultrasonic treatment is 40-120 kHz.

6. The method for chemically strengthening flexible glass according to claim 1, wherein: The cooling includes cooling by temperature reduction and natural cooling. The cooling rate is 2-5°C / min, and the temperature is cooled by temperature reduction to 100-105°C; and then naturally cooled to the ambient temperature.

7. A chemically strengthened flexible glass, characterized in that: The flexible glass is obtained by chemically strengthening the flexible glass according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Chemically strengthened lithium-aluminum-silicon microcrystalline glass as well as preparation method and application thereof

    CN116835890A